The Effect of Exercise Intervention Based Upon the Selective Functional Movement Assessment in an Athlete With Non-specific Low Back Pain: A Case Report and Pilot Study - Huang, Li; Liu, Haowei; Zhao, Li; Peng, Li (Frontiers in Psychology, 2020)
Objectives: To illustrate the effectiveness of the Selective Functional Movement Assessment (SFMA) as a guide to exercise intervention on chronic non-specific low back pain (CNLBP). Methods: A 23-year-old male volleyball athlete with CNLBP was evaluated using the SFMA to assess the degree of physical dysfunctions. And then two-stage exercise protocol was designed based on the results of SFMA. The athlete conducted the exercise intervention for 8 weeks, one hour each time, 3 times a week. Transverse abdominal muscles and multifidus muscle thickness, the degree of low back pain, and the degree of physical dysfunctions was measured at pre-, mid- and post intervention. Results: Based on the results of SFMA, the exercise protocol in the first 4-wk session was designed mainly to develop the mobility of ankle, hip and chest, and the stability of lumbar, hip and knee, in order to improve core strength and gluteal muscle strength; the second stage was an advanced stage with the increase of exercise load on the basis of flexibility and stability, its main purpose was to loosen the hamstring muscles and continue strengthening the core stability, and finally help the participant to establish the correct movement pattern and solve the problems of dysfunctions. After 8-wk exercise intervention, all movement patterns became functional/non-painful except the deep squat pattern; QBPDS score decreased from 11 to 2; VAS score decreased from 4 to 2; the thickness of transverse abdominis muscles（right side: 0.2cm vs 0.31cm, left side:0.22cm vs 0.33cm）and multifidus muscles (right side: 2.09cm vs 2.26cm, left side:2.15cm vs 2.29cm) were both increased. Conclusions: In this case, the SFMA helped to recognize problems related to mobility and stability on the hip joint, thoracic spine and even areas far away from the lumbar spine in an athlete with CNLBP that were not seen with more conventional examination procedures. The improvements of physical function, the increase of deep core muscles thickness, and the released pain after exercise intervention, all verified the effectiveness of SFMA to qualitatively analyze movement patterns at examination and to direct subsequent exercise intervention.